The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1002/tie.20103
|View full text |Cite
|
Sign up to set email alerts
|

Permissibility and use of options for hedging purposes in Islamic Finance

Abstract: The debate concerning permissibility and use of options in Islamic finance is ongoing, and the issue is far from settled. Current analyses on this issue appear to focus on taking of unnecessary risks ( gharar), the perceived lack of a physical asset in an options contract, and the possibility of exploitation of the ignorant. To the extent that these factors are involved, options are not permitted under Islamic teachings (the Shariah). In this article, we investigate whether options may be permitted for hedging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…He observes that in the absence of derivative markets, the funds belonging to Muslim investors may move to foreign markets to the detriment of community as a whole. Smolarski, Schapek, and Tahir (2006) highlight many advantages of derivatives contracts and claim that the criticism does not take into account various functions performed by them. To them, derivatives are beneficial in risk reduction and protect the buyers from financial loss.…”
Section: Developing Sharī'ah Compliant Financial Productsmentioning
confidence: 99%
“…He observes that in the absence of derivative markets, the funds belonging to Muslim investors may move to foreign markets to the detriment of community as a whole. Smolarski, Schapek, and Tahir (2006) highlight many advantages of derivatives contracts and claim that the criticism does not take into account various functions performed by them. To them, derivatives are beneficial in risk reduction and protect the buyers from financial loss.…”
Section: Developing Sharī'ah Compliant Financial Productsmentioning
confidence: 99%
“…Owing to the lack of professional expertise in the area, many banks in different countries stick to generic products like Mudarabah and Musharakah without taking into consideration customer preferences and market needs. Though hedging instruments are not been used extensively by IBs, Smolarski, Schapek, and Tahir (2006) studied alternatives from Islamic perspective and concluded that derivative choices might be allowed for supporting purposes in Islamic finance. They contended that if the basic financial service is itself admissible from Islamic perspective then there should be no problem in usage of derivative securities based on that financial service.…”
Section: Ibs Breakdown By World Regionmentioning
confidence: 99%
“…Arguments valid the acceptability of option contract a) (Smolarski, Schapek, & Tahir, 2006) argument emphasis on unnecessary risks (gharar) consumption, the anticipate lack of a physical asset in an options agreement, and tendency to manipulate the ignorant. They argue due to these issue, options may be permitted under Shariah teaching for hedging purposes as long as the economic underlying activities are themselves permissible (halal) from Islamic point of view.…”
Section: Analysis Of Islamic Optionsmentioning
confidence: 99%